PENGEMBANGAN MODUL PEMBELAJARAN FISIKA KONSTRUKTIVISTIK PADA MATERI DINAMIKA DAN KESEIMBANGAN BENDA TEGAR - Fitri Dwi Hartati; Zulirfan Zulirfan; Fakhruddin Z Fakhruddin Z (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : The aim of this research was to produce a valid constructivist physics learning module on dynamic and equilibrium of rigid body material as a source of physics learning media for senior high school students. The research used the Research and Development method following the ADDIE model. In this research, the module was developed over three steps out of five steps such as analysis, design, and development. The research data was obtained from the results of validation by five experts as validators. The validation module instrument was adopted by Badan Standar Nasional Pendidikan (BSNP) which consists of three feasibility aspect’s consist the content, the language, the graphic and present feasibility aspect’s. Validation was done through two phases which is the first and second phase. The content feasibility aspect got the average validity of 0.9 (valid with very good category), the language feasibility aspect was 0.92 (valid with very good category), and the graphic and present feasibility aspect’s was 0.90 (valid with very good category). In general, the indicator of each feasibility aspects has been valid and suitable with the development objectives. Based on the results of the validation, it can be concluded that the constructivist physics learning module on dynamic and equilibrium of rigid body material has been valid based on the content, the language, the graphic and present feasibility aspects and feasible as a source of physics learning media on dynamic and equilibrium of rigid body material.Keywords : constructivist module, dynamic and equilibrium of rigid body, physics learning of senior high school